Identifying a high-use hawksbill turtle habitat in the central Saudi Arabian Red Sea using photo-ID - Tanabe, Lyndsey K.; Cochran, Jesse E. M.; Hardenstine, Royale S.; Scott, Kirsty; Berumen, Michael L. (Frontiers in Amphibian and Reptile Science, 2025)
Hawksbill turtles (Eretmochelys imbricata) face significant threats globally, exacerbated by historical exploitation for their ornate carapace. In the Red Sea, data are lacking on many aspects of hawksbill turtle ecology. The in-water distribution of the species throughout the basin is relatively unknown, and essential habitats, such as foraging areas, are not well described. Here, we addressed this gap through photo-identification surveys conducted from July 2019 to December 2021 at Rabigh, located on the central Saudi Arabian coast of the Red Sea. Turtles were identified based on their unique facial scute patterns and subsequent re-sightings were used to describe their individual behavior and residency patterns. We analyzed photos from 104 sightings and identified 46 individuals. The majority of identified individuals were hawksbill turtles (n = 36), while green turtles were only occasionally reported (n = 10). Individuals exhibited diverse behaviors, including foraging (19%), resting (18%), and swimming (60%). Despite the small survey area, 42% of all turtles were re-sighted, suggesting that this site could serve as an important foraging habitat for this species. Notably, even on the last sampling day, we identified four new turtles, suggesting that with increased sampling effort, more individuals would likely be observed. These results highlight the importance of this location for critically endangered hawksbill turtles in the Red Sea, providing support for its designation as a protected area. This study also emphasizes the applicability of photo-ID monitoring to inform conservation strategies amid expanding coastal developments and increasing tourism in Saudi Arabia.